Calculated electron impact ionisation fragmentation patterns. (8th December 2021) - Graves, Vincent; Cooper, Bridgette; Tennyson, Jonathan
Abstract: There are many measurements and calculations of total electron impact ionisation cross sections. However, many applications, particularly in plasma physics, also require fragmentation patterns. Approximate methods of deducing partial cross sections are tested based on the use of total cross section computed within the well-used binary encounter Bethe approximation. Partial ionisation cross sections for three series of molecules including CH4, CF4 and CCl4 ; SiH4 and SiCl4 ; NH3 and PH3, were estimated using two methods. Method one is semi-empirical and uses mass spectroscopy data to fix the partial cross sections at a single electron energy. The second is a fully computational method proposed by Huber et al (2019 J. Chem. Phys. 150 024306). Comparisons with experimental results suggest that the mass spectroscopy method is more accurate. However, as Huber's method requires no experimental input, this method could be used as a first approximation when no experimental data is available. As mass spectroscopy sometimes provides incomplete datasets, a hybrid method based on the use of both methods is also explored.